2021
DOI: 10.3390/ijms22094942
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics, Photobiomodulation, and Disease Management: Controversies and Challenges

Abstract: In recent decades, researchers around the world have been studying intensively how micro-organisms that are present inside living organisms could affect the main processes of life, namely health and pathological conditions of mind or body. They discovered a relationship between the whole microbial colonization and the initiation and development of different medical disorders. Besides already known probiotics, novel products such as postbiotics and paraprobiotics have been developed in recent years to create ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 291 publications
(254 reference statements)
0
26
0
3
Order By: Relevance
“…According to the literature, H. pylori infection significantly affects the gastric microenvironment by several changes including DNA instability, disruption of NF-κB signaling pathway, as well as differentiation of autoreactive B cells and subsequent malignant transformation by genomic alternations [ 132 , 133 ]. In general, the use of probiotics effectively modulates immune responses, reduces gastritis by reducing pro-inflammatory cytokines, and ultimately prevents H. pylori -induced gastric malignancies [ 134 136 ].…”
Section: Probiotics As Anti- H Pylori Agentsmentioning
confidence: 99%
“…According to the literature, H. pylori infection significantly affects the gastric microenvironment by several changes including DNA instability, disruption of NF-κB signaling pathway, as well as differentiation of autoreactive B cells and subsequent malignant transformation by genomic alternations [ 132 , 133 ]. In general, the use of probiotics effectively modulates immune responses, reduces gastritis by reducing pro-inflammatory cytokines, and ultimately prevents H. pylori -induced gastric malignancies [ 134 136 ].…”
Section: Probiotics As Anti- H Pylori Agentsmentioning
confidence: 99%
“…It has been shown that the gut microbiome affects susceptibility to asthma, lung allergic responses, and chronic obstructive pulmonary disease [ 41 , 127 ]. Probiotics and their mechanisms of action in the prevention and treating respiratory diseases could be beneficial in the COVID-19 pandemic [ 128 ].…”
Section: Probiotics and Covid-19 Infectionmentioning
confidence: 99%
“…In den letzten Jahrzehnten haben Forschende auf der ganzen Welt intensiv untersucht, wie Mikroorganismen, die in lebenden Organismen vorkommen, die wichtigsten Lebensprozesse beeinflussen können [ 6 ]. Sie entdeckten einen Zusammenhang zwischen der gesamten mikrobiellen Besiedlung und der Initiierung und Entwicklung verschiedener biologischer Störungen.…”
Section: Ergebnisseunclassified
“…Neben bereits bekannten Probiotika wurden in den letzten Jahren neuartige Produkte wie Postbiotika und Paraprobiotika entwickelt, um neue nicht lebensfähige Mikroorganismen oder bakterienfreie Extrakte zu schaffen, die mit zusätzlicher Bioaktivität gegenüber Probiotika Vorteile bringen können, dies jedoch ohne hohes Risiko von Nebenwirkungen. Die multiple Interkonditionierung zwischen PBM, Probiotika und der menschlichen Mikrobiota, ihre Auswirkungen auf den menschlichen Körper und ihre Auswirkungen auf die Behandlung viraler Infektionskrankheiten sind von wesentlicher Bedeutung [ 6 ]. Gekoppelte komplexe PBM- und probiotische Interventionen können das Mikrobiom kontrollieren, die Aktivität des Immunsystems verbessern und das Leben von Menschen mit Immunstörungen retten.…”
Section: Ergebnisseunclassified